Ionization of hydrogen Rydberg molecules at a metal surface. - Lloyd, G; Procter, SR; Softley, T (2005)
The interaction of a beam of Rydberg molecules with a metal surface is investigated for the first time. Hydrogen molecules in a supersonic expansion are excited to Rydberg states with principal quantum number n, in the range 17-22 and are directed at a small angle onto a flat surface of either aluminum or gold. Detection of ions produced when Rydberg electrons tunnel into the metal surface provides information on the interaction between the Rydberg molecules and the surface potential. The experimental results suggest that, when close to the metal surface, the Rydberg molecules undergo a process of surface-induced rotational autoionization. It is found that the surface-ionization cross section shows strong resonances as a function of the applied electric field, which are independent of the metal studied.